(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the present study, spatial compound growth rates were estimated to know the growth pattern and instability in the area, production, and productivity of sugarcane in major sugarcane growing states of India. India ranks second in sugar production in the world due to favorable geographical conditions and social conditions for sugarcane production in India. For the said research, the manner in which the total production of the states in India has been studied